Tosylhydrazide-induced 1,6-enyne radical cyclization under copper catalysis: access to 3,4-dihydronaphthalen-1(2H)-one derivatives - Hosseini Nasab, Yeganeh Sadat; Rajai-Daryasarei, Saideh; Rominger, Frank; Balalaie, Saeed (The journal of organic chemistry, 2024)
We describe an approach to access 4-aroyl-3-aryl-3,4-dihydronaphthalen-1(2H)-one derivatives in 41-79% yields through the Cu-catalyzed radical cyclization/desulfonylation of 1,6-enynes with tosylhydrazide under air conditions. This alternative desulfonylation strategy combines mild conditions, external oxidant-free processes, and sustainability, contributing to more environmentally friendly organic synthesis. The mechanistic studies showed that the CuCl/O2 combination serves as the source of the oxygen atom needed to form the C═O bond. The existence of tosylhydrazide is crucial for this conversion.